Leprosy in children under fifteen years of age in the most hyperendemic municipality in Brazil - Ricardo Milhomem Costa; Marcela Silva Menezes; Maria Sortênia Alves Guimarães; Eliane Patrícia Pereira Franchi; Lorena Dias Monteiro; Mariana Caroline Tocantins Alvim (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To describe leprosy involvement and physical disability profiles in children and adolescents under 15 years old. Methods: Ecological time series study, based on data from the Brazilian Notifiable Diseases Information System, including new cases of leprosy residing in Palmas (TO), from 2001 to 2020. Results: A total of 471 notified cases in children and adolescents under 15 years of age were evaluated, resulting in a detection coefficient of 26.5 per 100,000 inhabitants. Of these, 52% (n=243) were women, 5% (n=24) corresponded to grade two disability, and 36% (n=168) were diagnosed through spontaneous demand. The temporal trend analysis showed a 0.5% reduction in the detection coefficient. There was a significant decrease in the diagnosis of the undetermined and tuberculoid clinical forms and a significant increase in the dimorphous form. Diagnosis through contact examination increased significantly by 13.1% and that through spontaneous demand decreased by 4.9%. The detection coefficient of cases with grade two disability reduced significantly by 7.4% while those with grade one increased by 16.8%. Conclusions: Despite the downward trend in the detection coefficient in children and adolescents under 15 years of age and in cases with grade two disability, other factors indicate failure in the adequate management of leprosy in Palmas.